THE ROLE OF PUBLIC CONTROL AND SOCIAL CONSCIOUSNESS IN INCREASING TAX COLLECTIVITY - Solikhova Khumora Khasan kizi (European Science Publishing, 2025)
This article scientifically examines the role of public oversight and social awareness in improving tax collection. The experience of Uzbekistan is comparatively analyzed with the practices of Scandinavian countries, the Republic of Korea, and Singapore. The research results show that citizens' trust in the tax system and active public participation directly affect the increase in tax collection rates. The article develops scientific and practical proposals for adapting international experience and enhancing tax culture in Uzbekistan.
Keywords: Tax collection, public oversight, social awareness, tax culture, Scandinavian experience, Republic of Korea, Singapore, Uzbekistan, tax system, trust.